2003
DOI: 10.1097/00000542-200305000-00009
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Point-of-Care Versus  Central Laboratory Measurement of Electrolyte Concentrations on Calculations of the Anion Gap and the Strong Ion Difference

Abstract: Results with two different measurement technologies differed significantly for plasma sodium and chloride concentrations. These differences significantly affected the calculated AG and SID values and might lead clinicians to different assessments of acid-base and electrolyte status.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
81
0
2

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(91 citation statements)
references
References 0 publications
8
81
0
2
Order By: Relevance
“…We are not the first to note differences in electrolyte concentration between ABG whole blood samples compared to venous plasma. Differences in sodium as well as chloride concentrations have been reported [5]. In this study, the observed difference could be traced back to consistently lower chloride concentrations in venous plasma samples compared to ABG and external quality control reference concentrations.…”
Section: To the Editorsupporting
confidence: 54%
See 1 more Smart Citation
“…We are not the first to note differences in electrolyte concentration between ABG whole blood samples compared to venous plasma. Differences in sodium as well as chloride concentrations have been reported [5]. In this study, the observed difference could be traced back to consistently lower chloride concentrations in venous plasma samples compared to ABG and external quality control reference concentrations.…”
Section: To the Editorsupporting
confidence: 54%
“…For now, a practical solution to obtain a workable situation was chosen: a correction factor for chloride concentrations measured on the chemistry analysers has been implemented. However, this is neither desirable nor necessary, as others have reported similar problems > 10 years ago [5]. Standardisation of sodium has been largely accomplished, it is now time for diagnostic companies to standardise chloride measurements as well.…”
Section: To the Editormentioning
confidence: 99%
“…The advantages and disadvantages of the various approaches to describing acid-base status (Table 2) have been the subject of several papers and reviews (64,77,78,79,158,160,212,217,232,255,290,293,336) Most of the criticism applied to the physicochemical approach is leveled at the errors inherent in the measurement of each independent variable, including those of each of the strong ions. Compared to other acid-base approaches, the physicochemical approach uses the largest number of measured variables because this approach intends to be as complete and accurate as possible.…”
Section: "Intricate Relationships Exist Between Arterial Blood Gasesmentioning
confidence: 99%
“…But, in the study of Mendel, prescription of Alfentanil caused to reduce bucking, coughing and hemodynamic effects after extubation without elongation of extubation time [22].…”
Section: Discussionmentioning
confidence: 96%